Equity and efficiency of health resource allocation in Sichuan Province, China - Minghua Zhou (BMC, 2024)
Abstract Background To analyze the equity and efficiency of health resource allocation in Sichuan Province and to provide a scientific basis for promoting health resource development. Methods Theil index, coefficient of variation, equalization index and health resource agglomeration degree (HRAD) were used to analyze the equity of health resource allocation, and data envelopment analysis (DEA) was used to analyze the efficiency of health resource allocation in Sichuan Province from 2017 to 2021. Results The Theil index and coefficient of variation of health technicians, licensed (assistant) physicians and registered nurses are larger than those of the number of beds, indicating that the equalization of the number of beds is relatively good. The equalization index of health resources in Sichuan Province ranges from 3.228 2 to 3.404 4 between 2017 and 2021, showing a gradually decreasing trend. The equalization index of Northwest Sichuan Economic Zone is the largest, indicating that the equity is relatively good. The equalization index of Chengdu Plain Economic Zone is the lowest, indicating that the equity is relatively poor. The HRAD of the number of beds, health technicians, licensed (assistant) physicians and registered nurses in Chengdu Plain Economic Zone, South Sichuan Economic Zone and Northeast Sichuan Economic Zone are all greater than 1, indicating that the health resources in these regions are better allocated by geography. The HRAD/ population agglomeration degree (PAD) of health technicians, licensed (assistant) physicians and registered nurses in South Sichuan Economic Zone, Northeast Sichuan Economic Zone and Panxi Economic Zone is less than 1, indicating that the health resources in these regions are insufficient relative to the agglomerated population. The comprehensive efficiency of health resource allocation in Sichuan Province and the five economic zones in 2020 is not 1, and the DEA is relatively ineffective. The Panxi Economic Zone, Northeast Sichuan Economic Zone and Northwest Sichuan Economic Zone all have relatively ineffective DEA. Conclusions From 2017 to 2021, health resources in Sichuan Province continue to grow, but equity has gotten worse. The degree of variation in the health resource allocation among the five major economic zones in Sichuan Province is large, with the Chengdu Plain Economic Zone having better equity in the health resource allocation by population and geography, and the Panxi Economic Zone and the Northwest Sichuan Economic Zone having insufficient equity in the health resource allocation by population and geography. The efficiency of health resource allocation in the Panxi Economic Zone, Northeast Sichuan Economic Zone and Northwest Sichuan Economic Zone needs to be improved.